Translating at the Court : Bartholomew of Messina and Cultural Life at the Court of Manfred, King of Sicily - Leemans, Pieter de (Book collections on Project MUSE., 2014)
"An important chapter in the rediscovery of Aristotle in the Middle Ages is the oeuvre of Bartholomew of Messina (Bartholomaeus de Messana), a translator at the court of Manfred, King of Sicily (1258-1266). However, the impact of both Bartholomew and Manfred on the cultural and intellectual life of their time remains understudied, especially in comparison to the attention received by the translator's contemporary, William of Moerbeke, and by the King's father, Frederick II of Hohenstaufen. This volume contributes to the exploration of this field of research in a twofold way. It discusses the nature and importance of Bartholomew's" -- page [4] of cover.